PENGARUH SLOW DEEP BREATHING TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI - pratiwi, anggi (IKesT Muhammadiyah Palembang, 2020)
Introduction: High blood pressure is becoming a significantly increasing public health problem. The incidence of hypertension in Indonesia is 34.1% and for Jakarta it is 35%. Hypertension can be treated by pharmacological and non pharmacological ways as well as by alternative therapies. Slow deep breathing is a technique of exercise and relaxation that helps maintain normal blood pressure. The aim of this study was to determine the effect of slow deep breathing on blood pressure among patients with hypertension. Methods: The design of this study was a one group pretest-posttest design. A sample of 15 respondents who were determined by purposive sampling technique. Data analysis using t-test dependent. Slow deep breathing exercises are given to respondents twice a day for one hour for one week. Blood pressure was measured with an electronic sphygmomanometer before and after the intervention in each sample. Results: Slow deep breathing exercise was effective in reducing systolic and diastolic blood pressure at these levels with a value of p <0.05. Discussion: Slow deep breathing can lower blood pressure with effect through the cardiovascular reflex control system and baroreflex sensitivity and a decrease in blood pressure. Key words: Hypertension, slow deep breathing, blood pressure